Management of Tethered Cord Syndrome; Our Experience at FJMU/SGRH - Muhammad Usman Anwar, Nabeel Choudhary, Talha Abbas, Rida Zahid, Adeel-Ur-Rehman, Mohammad Faheem Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tethered cord syndrome (TCS) is a neurologic condition characterized by abnormal traction of the spinal cord, leading to progressive neurological, urological, and orthopedic deficits. Objective: To evaluate the clinical presentation, operative management, and postoperative outcomes of patients undergoing surgical treatment for tethered cord syndrome at a tertiary neurosurgical center. Methods: A retrospective case series was conducted at the Department of Neurosurgery, Sir Ganga Ram Hospital/Fatima Jinnah Medical University, Lahore, from June 2019 to December 2021. Ten patients (3 males, 7 females), aged 2 to 26 years, were included. Five had lipomyelomeningocele and five had occult tethered cord diagnosed clinically and confirmed on MRI. Results: Neurological improvement was noted in 7 patients (70%). Three patients (30%) showed no change but remained neurologically stable. Two patients (20%) developed transient urinary obstruction postoperatively, which resolved within two months. No patient experienced postoperative neurological deterioration, cerebrospinal fluid leak, or infection. Conclusion: It is concluded that surgical detethering is a safe and effective intervention for tethered cord syndrome, resulting in high rates of neurological improvement and minimal complications. Patients with tethered cord should be operated irrespective of age and neurological deficit, as timely intervention can prevent further deterioration and improve quality of life. Continued multidisciplinary follow-up is essential for monitoring long-term outcomes. Keywords: Tethered cord syndrome, lipomyelomeningocele, spinal dysraphism, neurological outcomes.